Being, Negotiating, Mending: Experiences of Care in Neoliberal Times - Cameron, Keri (My University, 2020)
The purpose of this study is to explore care in Ontario, Canada from the perspective of patients. I took on the roles of both a patient and a researcher, exploring the current state of care as a patient who has navigated the health system and as a researcher with background in disability studies and social geography. I use feminist auto/ethnographic methods, including observation and fieldnotes, journaling, memory, and notes in my patient records as data. I also conducted semi-structured in-depth interviews with seven individuals who underwent hip or knee replacement surgery and two family members who provided informal care to individuals post-operatively. I have organized data using three storylines: being patient, negotiating care, and mending fault lines. There are two layers of my analysis: our individual encounters with carers alongside our changing embodiment and the broader care relations of the system, increasingly influenced by neoliberalism. Care is increasingly informalized and commodified as austerity measures cut public financing for care and services are de-listed. Neoliberalism produces poor and precarious working conditions for nurses and personal support workers and this translates into insufficient care for patients and support for families. With care increasingly being shifted to the home and community, individuals and families are taking on more responsibility in terms of caring for family members.
Keywords: healthcare, care, lived experience, neoliberalism, ethnography, autoethnography, austerity